The Effectiveness of PT Pertamina Patra Niaga Fuel Terminal Ternate's CSR Program in Improving Traditional Fishermen Welfare in Ternate - Citra Lesmana Simanjuntak; Leonardus Watratan; Muhammad Iqbal (Global Writing Academica Researching and Publishing, 2025)
Fish Aggregating Devices (FADs) are artificial structures that aid fishermen in catching fish using traditional methods. However, conventional FADs are often made from materials that do not break down easily, which can harm marine ecosystems by creating long-lasting debris. This study examines the Pena Laut program, which aims to support traditional fishermen while protecting the marine environment. Specifically, the research assesses the effectiveness of Corporate Social Responsibility (CSR) initiatives and new, eco-friendly fishing gear in Ternate waters. Using documentation and observation, the study sampled 18 program beneficiaries and applied a qualitative descriptive method. Community Satisfaction Index (CSI) data were collected through surveys. The findings reveal that the CSR program from PT Pertamina Fuel Terminal Ternate has had a positive impact on the welfare of fishermen. Activities in the program include forming fishing groups, installing infrastructure, providing cooperative training, and producing eco-friendly products. The survey indicates that the program is operating effectively, with an CSI score of 3.77, or 94.19% when converted, which is considered very good. To ensure continued productivity and sustainability, a new portable, environmentally friendly FAD was developed. This innovation has enabled fishermen to increase their catches, resulting in a 30% rise in community income, equivalent to approximately IDR 150,000 per month, an increase from IDR 500,000 to IDR 650,000.